Variation in cytochrome-b haplotypes suggests a new species of Zygodontomys (Rodentia: Cricetidae) endemic to Isla Coiba, Panama - González,Publio (2010)
The identity of two insular populations of rodents of the nominal species, Zygodontomys brevicauda (Allen & Chapman, 1893), from the Veragua Archipelago was examined. The mitochondrial cytochrome-b gene was sequenced from specimens collected on Isla Coiba (n = 10), Isla Cébaco (n = 3) and on the nearby Peninsula Azuero (n = 3) in Panama and compared with sequences of Z. brevicauda and a number of other related species from GenBank. For Panama, phylogenetic analyses identified two clades within Zygodontomys Allen, 1897; one representing Isla Coiba and another clade composed of rats from Isla Cébaco and from the mainland on the Peninsula Azuero, as well as a GenBank sequence of Z. brevicauda from Venezuela. We suggest that the population from Isla Coiba may represent a previously undescribed species of sigmodontine rodent that is endemic to this Pacific Island.